Correlation and path coefficient analysis for yield and its related traits in sesame (Sesamum indicum L.) genotypes - Takele, Feyera (Journal of Science and Development, 2021)
Forty nine sesame genotypes were evaluated in simple lattice design at Bako and Uke during 2018 cropping season. The objective of the study was to estimate the extent of associations between yield and its related traits. The combined analysis showed highly significant differences among the genotypes for all studied traits. Both phenotypic and genotypic correlation coefficient analyses showed positive and significant association of seed yield with plant height, branches per plant, capsule per plant, biomass yield and harvest index. On the other hand, the association of bacterial blight with grain yield was negative and highly significant at both phenotypic and genotypic levels. Biomass yield, harvest index and capsule per plant had high and positive direct effect on grain yield. The result of the study showed that biomass yield, harvest index and capsule per plant were the very important yield related traits that should be considered for sesame seed yield improvement.